Psychology of leadership in business - Hura, Tatiana Vitaliivna; Romanovsky, Oleksandr Heorhiiovych; Knysh, Anastasiia Yevhenivna (Національний технічний університет "Харківський політехнічний інститут", 2025)
The conceptual foundations of leadership in order to formulate students' competencies are examined in the textbook: to understand the theoretical provisions of the modern leadership paradigm and the practical experience of world and national leaders; to know the characteristics of types and styles of leadership; to be able to identify leadership potential, self-esteem of a business leader; to develop emotional intelligence, charismatic abilities. Particular attention is paid to the scientific concepts of leadership in ancient times and to the present day; emotional, charismatic, transactional and transformational leadership. The individual psychological characteristics of a business leader in order to formulate students' competences are also revealed in an accessible form: developing the ability to apply in practice the knowledge gained on the development of cognitive qualities of a business leader, the ability to work in a team, taking into account the personal traits of a business leader, managerial, gender, and cross-cultural aspects. The authors draw attention to the importance of neuro-linguistic programming in business leadership, the peculiarities of management organisation in business structures. The target audience is current and potential private entrepreneurs, business leaders, international university students, and anyone who wants to succeed in any field of business. The manual is intended for students of all specialities studying in a foreign language and postgraduate students.
Keywords: textbook; business; psychology; psychology of leadership; concept of leadership; definitions of leadership